THE EFFECT OF ORDINARY BENZENEON THE OSSIFICATION CENTERS IN THE LONG BONES OF MICE EMBRYOS - Fawzi S. AL- Asadi; Majdi Faisal Majeed; Haifa Ali Hussan (Basrah Journal of Veterinary Research)
Present study was to detect the ordinary benzene on ossification in the long bones of themouse embryos Musmusculus L.conducted the current study, 56 mice adult (16 male& 40female) the females were divided into four groups, first for the control of the three treatmentgroups wasexposed to ordinary benzene concentration (4.5ppm, 9ppm, 45ppm) hours / dayfor 45 days and then married with intact males and took 20-day embryos,the results refer thatthe treatment groups showed significant decrease p< o.o5 revealedin the centers ofossification compared with control group.